Confucianism and corporate awareness of climate change - Bin Li; Yunzhi Lin; Wendai Lv (China Journal of Accounting Research)
Drawing on practice theory and Confucian ecological philosophy, this paper explores the relationship between Confucianism and corporate climate change awareness. Using a sample of Chinese A-share listed companies, we find that companies more influenced by Confucianism exhibit stronger climate change awareness. This positive relationship is further strengthened by government environmental governance. Impact channel tests show that Confucianism enhances corporate climate change awareness by promoting humanism, deontology and collectivism. Heterogeneity analysis shows that the positive correlation between Confucianism and climate change awareness persists in both non-carbon-intensive industries and struggling companies. Lastly, economic consequence tests indicate that Confucianism helps reduce corporate carbon emissions by enhancing climate change awareness.